Experimental investigation on low-velocity-impact and post-impact-tension behaviors of GFRP T-joints after hydrothermal aging - You Peiyu; Liu Cuilong; Yao Xiaobang; Xu Kaixin; Li Mingjie; Wu Ye; Luo Jixiang (e-Polymers)
As an integrated structural unit, composite T-joints are used to transfer the load between two vertical planes, such as the wing box of an aircraft. The article aims to investigate the failure mechanism of the glass fiber-reinforced polymer (GFRP) composite T-joints subjected to low-velocity impact on the weak deltoid and post-impact tension after hydrothermal aging. First, the improved vacuum-assisted resin infusion suitable for the fabrication of GFRP T-joints is employed. Second, the hydrothermal aging is conducted at 25°C and 65°C with the same relative humidity of 85% for 1–6 weeks. Finally, the impact resistance and tensile strength are analyzed based on response history and damage morphology. The results show the significant degradation of impact strength and stiffness of GFRP T-joints after hydrothermal aging and with the increase in aging time and temperature. In the failure mode of post-impact tension, the interlaminar cracks in the deltoid propagate in the horizontal and vertical directions, and there is a large gap in horizontal crack length between aged and non-aged T-joints.